Pengujian Toksisitas Akut Oral Dan Dermal pada Biolarvasida Metarhizium anisopliae terhadap Tikus Putih Spraque Dawley - Deni Zulfiana (Al-Kauniyah: Jurnal Biologi, 2014)
Acute oral and dermal toxicity test against white rats was conducted to determine the toxicity and side effects of bio-larvacide (Metarhizium anisopliae crude extract) on humans. In the oral test used a maximum dose 5000 mg/kg and dermal testing used a maximum dose of 2000 mg/kg. Dose treatment and control tested to 5 Spraque Dawley male rats. The results showed that oral treatment with a dose of 5000 mg/kg did not cause mortality and did not cause changes in anatomic pathology of viceral organs. In the dermal treatment with a dose of 2000 mg/kg did not cause mortality and did not cause changes in anatomic pathology of viceral organs. Based on these results LD50 acute oral M. anisopliae biolarvacide above 5000 mg/kg and the acute dermal is above 2000 mg/kg. It was therefore concluded that the formulation of Metarhizium anisopliae biolarvasida classified as not hazardous when used in accordance with the recommendation of the class I (WHO, 2003).